Reabilitaciâ nacizma kak proâvlenie èkstremizma: voprosy kvalifikacii po ugolovnomu i administrativnomu pravu Rossijskoj Federacii - Potapkin, Sergey N. (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
The article is devoted to the issues of qualifying actions related to the rehabilitation of Nazism under the Criminal Code of the Russian Federation as manifestations of extremism. The issues of the formation of the practice of application of art. 354.1 of the Criminal Code of the Russian Federation are being analyzed, as well as the delimitation of the rehabilitation of Nazism from related crimes and administrative offenses.
Keywords: działalność ekstremistyczna; organizacja terrorystyczna; organizacja ekstremistyczna; nazizm; rehabilitacja nazizmu